Developing a Teaching Methodology of Translation Course : A Cooperative Learning Model for English Department Students - Novitasari, Fransisca; Ardi, Priyatno (Magister Kajian Bahasa Inggris (English Language Studies) Universitas Sanata Dharma Yogy, 2016)
The article, firstly, analyzes some basic concepts of translation and cooperative learningmodel. Further, a design of translation course’s syllabus for an undergraduate level isdescribed. In addition, an example of lesson plan and an example of students’ analysis areelicited. The teaching methodology consists of a step-by-step procedure which adopts thecooperative learning model. In this cooperative learning model, the educator is understood asa facilitator, whose role is providing the materials, checking the students’ understanding,giving feedback, and evaluating the failures and the weaknesses of the knowledge-transferprocess.Therefore, the transfer process of translation theory and practice is mainlyaccomplished by the students, collectively and individually. Overall, the implementation ofcooperative learning model in the design and procedure of translation course is viewed as aneffective way to improve the ability of students in translating English text into Indonesian andin translating Indonesian text into English.Keywords: translation course, cooperative learning, undergraduate level